Alternating-current relaxation of a rotating metallic particle - 聂国熹 田文佳 黄吉平 顾国庆 (Chinese physics B, 2016)
Based on a first-principles approach,we establish an alternating-current（AC） relaxation theory for a rotating metallic particle with complex dielectric constant εα=εα-iσα/ω0.Here εα is the real part,σα the conductivity,ω0 the angular frequency of an AC electric field,and i=-11/2.Our theory yields an accurate interparticle force,which is in good agreement with the existing experiment.The agreement helps to show that the relaxations of two kinds of charges,namely,surface polarized charges（described by εα） and free charges（corresponding to σα）,contribute to the unusually large reduction in the attracting interparticle force.This theory can be adopted to determine the relaxation time of dynamic particles in various fields.